THE EFFECT OF DIFFERENTIATION STRATEGY, MARKET ORIENTATION, PRODUCT QUALITY, AND PRICE PERCEPTION ON COMPETITIVE ADVANTAGE IN THE TIKTOK SHOP MARKETPLACE - Nidia Putri Callistasari; Lukita Tripermata; Lesi Hartati (Universitas 17 Agustus 1945 Surabaya, 2026)
The development of social media–based e-commerce has intensified competition among marketplaces, including TikTok Shop, which adopts a social commerce concept. This condition requires business actors to possess sustainable competitive advantages in order to survive in the dynamic digital market. This study aims to analyze the effect of differentiation strategy, market orientation, product quality, and price perception on the competitive advantage of the TikTok Shop marketplace among the community in Palembang City. This research employs a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to active TikTok Shop users in Palembang City using purposive sampling techniques. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results indicate that, partially, differentiation strategy has a positive and significant effect on the competitive advantage of the TikTok Shop marketplace. Market orientation has a positive and significant effect on competitive advantage. Product quality also has a positive and significant effect on competitive advantage. Furthermore, price perception has a positive and significant effect on the competitive advantage of the TikTok Shop marketplace.